Alumni Mahaiswa Program Doktor Ilmu Ekonomi Pascasarjana Untag 1945 Surabaya - Burhan, Lalu (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2008)
This research focus on TFR, CPR, Empowerment of family economic and Family welfare inWestNusatenggaraProvince. The question is could the Family Planning (TFR and CPR) increase efectivity of the Family economis and family welfare inWestNusaTenggaraProvince? Leibenstein (1958) in His fertility theory said factors which determine amount of birth which expected family are parents. According Becker (1960, 1963) with his demand theory strengthen by Ananta (1981) that fertility assumed as commodity (Consumer Durable) like threated commudity in economic. In demand theory one of variable which determine are income and in using simple preference theory, and can describe by two dimension graph with Indifference curve (Becker and Ananta 1960, 1981). Terance J. Hull (1976-1978) and Masri Singarimbun (1976), in their research connected with Fertility and social ekonomi strata. Birsall dan Sanding dalam Sri Murtiningsih (2005) talking about fertility, Increme percapita and welfare. Related with this desertation research that variable which research are CPR and TFR variable and its influences toward efectivity family economic and family welfare programme, which mean value of children and first time marriage in one family/TFR and join in Family Planning including Unmetneed/CPR, could have a positive influences toward efectivity family economic and family welfare programme which expected will find a model concept and find a variable which have a significant influence between every variable. This desertation constitute develop from becker (1960), Ronald Freedman (1975), J. Bongaart theory (1978), with proximate determinants of fertility, Leiberstain (1958), Birsall dan sanding dalam Sri Moertiningsih (2005) Terance J. Hall (1976-1978), and Becker strengthen by ananta which focuses in advantage value from additional child in one family relate with productivity from child birth according to parts of this theory push the power of increasing family welfare in one family are fertility and economic recovery which described in this research with  TFR, CPR and family economical (UPPKS). Increasing of education level, quality of health with general caused by modernism process give motivation to women or eligible couple to limited the amount of their child, then their have knowledge which needed in using contraceptive as family Planning method. Related with this finding research that higher CPR then lower the child in one family which analogize with the decrease of TFR (Total Fertility Rate). This research population are all eligible couple in West Nusa Tenggara Province and research sample are 200 Family/eligible couple take by multistage purposive random sampling, with divide 4 district according its region and divide become 4 kwadran are: Kwadran I, II, III, IV, based BKKBN count. The data collect by spreading open questioner with continue scale. The questioner examined to 30 people to get good data, through validity test and reability by SPSS version 11.00, that data have fulfillment to analyze with SEM, with software AMOS 4.01 version. Theority test based on theory and first result research. The desertation found : Comprehensively from variables research in all hypothesis accepted and examined significantly, and new model that explain research model aboaut welfare. Based on analysis and structural model from this research, show that model which get by base emphiric data have fulfill the classification (Goodness of Fit). And this finding and from research model inspected relly that CPR, TFR and family economic/UPPKS strong enough and effective as determination in effort to increase family economic current user. What we get from this research basically with theories or results of othe research. If we inspect the variables of CPR, TFR and family economic/UPPKS, in partial or simultance, influence toward family economic are very significant. This influences have two reason: first, factor which determine good or bad of increase of family economic are the effort on CPR participants, TFR which have good control, that term give influences on strengthen better family economic/UPPKS. Second in the three variables (CPR, TFR, and UPPKS) UPPKS have lower influence than CPR and TFR factors participant can manage in good handle, in directly can give effect toward increase of family economic. Although the effort of UPPKS significantly need more concern to increase family economic. That all about influences TFR and CPR factor toward effectivity family economic related with increase family welfare on West Nusa Tenggara people. Otherwise the activities of influence toward family income as a factor of more attention in term of supporting increasing family welfare of family planning acceptors.